2004
DOI: 10.1111/j.1467-9701.2004.00595.x
|View full text |Cite
|
Sign up to set email alerts
|

Donor Funding of Multilateral Aid Agencies: Determining Factors and Revealed Burden Sharing

Abstract: The paper reports an empirical study of the factors affecting burden sharing among OECD's 22 DAC members in 'bankrolling' the multilateral aid agencies. These are the UN agencies, World Bank's IDA and non-IDA programmes, regional development banks, European Community, and other multilateral agencies that include the Global Environmental Facility and the Montreal Protocol on environment. Annual data over 1970-2000, pooled across the donor countries, form the basis for the empirical estimation of each donor's sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Small countries favor the multilateral organizations but the parameter α is close to one and certainly not so small as the parameter presented in Table 4a. The latter finding is in line with what Addison et al (2004) report who reviewed the exploitation hypothesis for multilateral aid agencies. They find clear signs of 'reverse exploitation', where donor governments of small economies carry a disproportionately large share of the funding burdens of multilateral agencies.…”
Section: Sharing Of Burdenssupporting
confidence: 79%
See 1 more Smart Citation
“…Small countries favor the multilateral organizations but the parameter α is close to one and certainly not so small as the parameter presented in Table 4a. The latter finding is in line with what Addison et al (2004) report who reviewed the exploitation hypothesis for multilateral aid agencies. They find clear signs of 'reverse exploitation', where donor governments of small economies carry a disproportionately large share of the funding burdens of multilateral agencies.…”
Section: Sharing Of Burdenssupporting
confidence: 79%
“…Such a measure would boil down to the contributor's share of the total contribution by all members, as shown in Table 2.The following null hypothesis is relevant: each donor gives money that is equal to its share in total GDP of all donors. To the test the burden sharing hypothesis we follow the approach of Addison et al (2004) who examined burden sharing in the case of multilateral foreign aid and found some traces of 'reverse exploitation': the small countries support multilateral agencies disproportionately. The ability to pay is the starting point for the estimation exercise, but…”
Section: Sharing Of Burdensmentioning
confidence: 99%
“…However, Addison et al (2004) point out that the leve l of per capita income can also affect a donor's desire and the demand for a public good or, in the case of Addison et al, the services of a particular multilateral agency. The latter effect can possibly work in the opposite direction of the ability-to-pay effect.…”
Section: H0mentioning
confidence: 99%
“…family planning. The government size is perhaps an imperfect proxy as a driving force for development aid, but it is nevertheless stressed by Addison et al (2004) that a member's ability to bear financial responsibility for development aid commitments depends on the size of the public sector in that country. The relationship is straightforward: the capacity to fund development aid programs depends very much on the government's ability to tax and the more a government can tax the easier it can finance aid programs.…”
Section: Explaining the Level Of Disbursementsmentioning
confidence: 99%
See 1 more Smart Citation